Getting started with MicroStation 10 CONNECT : learning the interface and settings, and using tools and techniques to create 2D drawings - Mann, Peter (O'Reilly, 2016)
"MicroStation, the high-end CAD software developed by Bentley Systems, has capabilities ranging from simple 2D drawings to highly-complex photorealistic 3D projects. In this video, you'll learn about MicroStation CONNECT and how to use the application's 2D tools and drawing techniques. Instructor Peter Mann starts with the fundamentals, taking you through opening and saving new documents, discovering the different views, and understanding what elements are and how to control them. You'll then move into an explanation of AccuDraw, MicroStation's most important tool. You'll learn to create shapes, scale, rotate, work with annotations and text, and finish with instructions for plotting and printing your completed designs. The course includes access to working files containing drawing exercises, drawing set-ups, and a real architectural floor plan so you can practice your new skills."--Resource description page.